Mobile Field Service Engineer Application - Budholia, Akash; Mehta, Rishit; Godhrawala, Murtaza; Shaikh, Zaheed (International Journal of Computer Sciences and Engineering, 2025)
The mobile devices of this generation are head to head with high-end desktops in terms of processing power, memory management schemes, overall usability etc. It won't be surprising to see the industries do away with desktops or even laptops and employ mobile devices given the promise these devices have shown in the last few years. Automation is the need of the hour, and these mobile devices go a long way to help achieve that. These mobile devices can also be employed at places where saving time helps to increase productivity such as maintenance of power plants. Also, an access to real-time data helps the engineer get a much detailed view of the overall working and extent of the problem, if any. Hence to simplify the overall procedure, in this paper, we present a mobile solution to help the Field Engineer automate the task of carrying out the maintenance activity even when connectivity is limited, with the help of mobile device and related technologies which help to transfer data from one end to another.